Perception of Staff on Internal Audit: A Case Study in Northern Provincial Council of Sri Lanka - Anojan, V.; Nimalathasan, B. (9th International Conference on Education, 2020)
The main purpose of this study is to reveal the perception of staff on internal audit in Northern Provincial Council of Sri Lanka. Internal audit mainly ensures the effective and efficient of operations, increase quality and user’s reliability on the financial reporting and legal compliance of the firm. Questionnaire used in this study which was collected from government officers who work in Northern Provincial Council of Sri Lanka through a 5 points Likert scale questionnaire covering eight major areas of internal audit, internal audit report, accountability & transparency, internal auditor’s independence, competence of auditor, materiality, audit evidence, true and fair view, performance audit and resources & facilities. Descriptive and inferential analysis performed with the help of SPSS latest version in this study. Mean analysis confirmed that perception of staff on internal audit report and audit evidence are in satisfactory level other areas of internal audit are below than satisfactory level in Northern Provincial Council of Sri Lanka. Independent sample t-test revealed that there is mean difference between perception of head of the department/division and perception of chief internal auditor/ internal auditor/ internal audit staff on internal audit in Northern Provincial Council of Sri Lanka however which is not a significant mean difference. According to the staff’s perception, accountability & transparency, internal auditor’s independence, competence of auditor, materiality, true and fair view, performance audit and resources & facilities utilization of internal audit should be improved. It will lead for the effective and efficient operations, increase quality and reliability of financial reporting and legal compliance of Northern Provincial Council.
Keywords: Audit Report; Internal Audit; Perception